Gestures, Vocalizations, and Memory in Language Origins - Aboitiz, Francisco (Frontiers in Evolutionary Neuroscience, 2012)
This article discusses the possible homologies between the human language networks and comparable auditory projection systems in the macaque brain, in an attempt to conciliate two existing views on language evolution: one that makes emphasis on hand control and gestures, and the other that makes emphasis on auditory-vocal mechanisms. The capacity for language is based on relatively well defined neural substrates whose rudiments have been traced into the non-human primate brain. In its core, this circuit makes up an auditory-vocal sensorimotor circuit with two main components, a “ventral pathway” connecting anterior auditory regions with anterior ventrolateral prefrontal areas, and a “dorsal pathway” connecting auditory areas with parietal areas and with posterior ventrolateral prefrontal areas via the arcuate fasciculus and the superior longitudinal fasciculus. In humans, the dorsal circuit is especially important for phonological processing and phonological working memory, capacities that are critical for language acquisition and for complex syntax processing. In the macaque, the homologue to the dorsal circuit overlaps with an inferior parietal-ventrolateral prefrontal network for hand and gestural action selection that is under voluntary control, while vocalizations are largely fixed and involuntary. The recruitment of this dorsal component for vocalization behavior in the human lineage, together with a direct cortical control of the subcortical vocalizing system, are proposed to have marked a fundamental innovation in human evolution, generating an inflection point that permitted the explosion of language and human communication. In this context, vocal communication and gesturing have a common history in primate communication.